Industri Pasar Uang Syariah di Asia Tenggara - S, Suzana; Despileny, Iren; S, Syahpawi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to analyze the Islamic money market in the context of Islamic economics in Southeast Asia. Understanding the definition of Islamic money market, its functions, mechanisms, objectives, as well as the instruments used in the Islamic money market. In addition, this research also highlights the importance of the money market in meeting the working capital and liquidity needs of companies in accordance with Islamic principles. This research uses the literature study method, collecting information and data through literature studies and conducting content analysis from various sources relevant to the money market in the context of Islamic economics in Southeast Asia. The data collected was analyzed using a qualitative approach, which involved coding, data reduction, and conclusion drawing. In this context, Islamic money markets are considered an important alternative in a financial system that adheres to Shariah principles.